Reliability, validity and minimal detectable change of the Mini-BESTest in Greek participants with chronic stroke. - Lampropoulou, Sofia I.; Billis, Evdokia; Gedikoglou, Ingrid A.; Michailidou, Christina; Nowicky, Alexander V.; Skrinou, Dimitra; Michailidi, Fotini; Chandrinou, Danae; Meligkoni, Margarita (Physiotherapy Theory & Practice, 2019)
Objectives: This study aimed to investigate the psychometric characteristics of reliability, validity and ability to detect change of a newly developed balance assessment tool, the Mini-BESTest, in Greek patients with stroke. Design: A prospective, observational design study with test-retest measures was conducted. Methods: A convenience sample of 21 Greek patients with chronic stroke (14 male, 7 female; age of 63 ± 16 years) was recruited. Two independent examiners administered the scale, for the inter-rater reliability, twice within 10 days for the test-retest reliability. Bland Altman Analysis for repeated measures assessed the absolute reliability and the Standard Error of Measurement (SEM) and the Minimum Detectable Change at 95% confidence interval (MDC95%) were established. The Greek Mini-BESTest (Mini-BESTestGR) was correlated with the Greek Berg Balance Scale (BBSGR) for assessing the concurrent validity and with the Timed Up and Go (TUG), the Functional Reach Test (FRT) and the Greek Falls Efficacy Scale-International (FES-IGR) for the convergent validity. Results: The Mini-BESTestGR demonstrated excellent inter-rater reliability (ICC (95%CI) = 0.997 (0.995-0.999, SEM = 0.46) with the scores of two raters within the limits of agreement (meandif = −0.143 ± 0.727, p > 0.05) and test-retest reliability (ICC (95%CI) = 0.966 (0.926-0.988), SEM = 1.53). Additionally, the Mini-BESTestGR yielded very strong to moderate correlations with BBSGR (r = 0.924, p < 0.001), TUG (r = −0.823, p < 0.001), FES-IGR (r = −0.734, p < 0.001) and FRT (r = 0.689, p < 0.001). MDC95 was 4.25 points. Conclusion: The exceptionally high reliability and the equally good validity of the Mini-BESTestGR, strongly support its utility in Greek people with chronic stroke. Its ability to identify clinically meaningful changes and falls risk need further investigation.